(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Steroid derivatives’ ability to bind to hormone-related receptors and stop the growth of cancer cells makes them promising anticancer medications. The efficacy of a new class of dioximino androstene derivatives against three distinct cancer cell lines—the brain cancer cell line SF-268, the lung cancer cell line NCI-H460, and the breast cancer cell line MCF-7—was evaluated in this investigation. To determine if these substances were cytotoxic, we used the MTT assay. Cell viability was evaluated after 48 hours of treatment with a consistent dosage. Studies on the structure-activity relationship (SAR) have shown that certain oxime substitutions at C (3) and C (17) significantly increased cytotoxicity. Furthermore, the findings demonstrated significant growth inhibition for certain dioximino androstene derivatives. Molecular docking studies revealed that these drugs have strong interactions with significant cancer-related protein targets. Furthermore, dioximino androstene derivatives offer therapeutic potential and are excellent candidates for the development of anticancer drugs, according to the ADME/Tox data. To optimise these compounds for medicine, further thorough study is strongly recommended, including in vivo evaluations.